Synergistic effects of segregated network by polymethylmethacrylate beads and sintering of copper nanoparticles on thermal and electrical properties of epoxy composites - Bae, Young-Han; Yu, Min-Ji; Vu, Minh Canh; Choi, Won Kook; Kim, Sung-Ryong (ELSEVIER SCI LTD, 2018)
We present a simple method to improve the thermal and electrical conductivity of epoxy composites via sintering of formic acid-treated Cu nanoparticles (NPs) in the presence of polymethylmethacrylate (PMMA) beads. The surface-treated Cu NPs, epoxy, and PMMA beads were mixed and then sintered under 20 MPa of pressure at 200 degrees C. The morphology of the Cu NPs and the thermal conductivity, volume resistivity, and thermal stability of the epoxy composites were investigated. The significant improvement of the thermal and electrical conductivity of epoxy composites was attributed to segregation of the Cu NPs between PMMA beads and sintering of neighboring Cu NPs. At 30 wt% of Cu NPs, the thermal conductivity of the epoxy composites was 1.05 W/mK, and the volume resistivity was 5.9 x 10(10) Omega cm at a (bead)/(epoxy + bead) ratio of 0.6. The thermal stability of the composites increased with. increasing cross-linked PMMA bead content. Low-temperature sintering of formic acid-treated Cu NPs in the presence of PMMA beads affords an innovative way to improve the thermal and electrical conductivity of the composites. (C) 2017 Published by Elsevier Ltd.
Keywords: CONDUCTIVITY; BEHAVIOR; INTERFACE; NANOCOMPOSITES; OXIDATION; RESIN; ACID